Peran Reserse Dalam Penyidikan Terhadap Tindak Pidana Pencurian Yang Dilakukan Oleh Anak (Studi Kasus di Polres Ngawi) - Permata, Petty Dyah, Hartanto, S.H.,M.Hum, Bambang Sukoco, S.H (2015)
Act No. 11 of 2012 on the Child Criminal Justice System shows the protection of the rights of children as the future generation by prioritizing restorative justice. This research aims to describe the role of a detective in the investigation of criminal offenses of theft by children at the Ngawi District Police Station, according Act No. 11 of 2012 on the Child Criminal Justice System and obstacles which encountered by the detective in Ngawi District Police whilst investigating criminal offenses of theft committed by children. The type of research is juridical empirical research methods to obtain primary data and find the truth or the facts and reviewing the juridical on the descriptive. Analysis of data on legal writing is usually done through a qualitative approach. The results showed that the role of a detective in the investigation of criminal offenses of theft under the Act No. 11 of 2012 on the Child Criminal Justice System done with the first step of investigation, enforcement, inspection, completion and submission of the case file. After everything has examined by the investigators then the filing conducted, which then the case file submitted to the prosecutor's office where the crime scene happened/locus delicty, if it is correct then the POLRI stamp will be stamped on and will be returned for completion if it is incomplete. Other obstacles faced by investigators in prevention of criminal offenses committed by children are: skills and way of workings of the child investigator / police investigator in any criminal investigation process when the child is associated with the diverse education they have received, conditions of facilities in Ngawi District Police station given by the official, and lack of insight or knowledge of parents and the public about the dangers of the criminal offenses of children to their mental and psychological development.